The vegetation of Slovenia and northern Istria in late prehistory - Andrič, Maja (Arheološki vestnik, 2004)
In the late prehistory, climatic fluctuations and human activityassociated with transition to farming and metallurgy triggeredsignificant changes in vegetation and in the palaeoenvironment.However, the reasons for these vegetation changes and mech-anisms, which led to the formation of present-day culturallandscape are still poorly understood. This paper presents theresults of pollen analysis at three palaeoecological sites, locat-ed in four different phytogeographic regions of Slovenia andnorthern Istria. The results indicate that, while the landscapein late prehistory became increasingly open due to forest clearanceand burning, the biodiversity also increased. Changes of for-est composition also occurred, and the increase in fir pollenmight be associated with increased precipitation and possiblyless intensive forest pasture